2015
DOI: 10.5694/mja14.01674
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Genetics Clinic: a model for multidisciplinary genomic medicine

Abstract: Objectives: To describe patient characteristics, standard operating procedure, and uptake of genetic testing at the multidisciplinary Cardiac Genetics Clinic (CGC) at the Royal Melbourne Hospital during its first 6 years. Design: Database exploration of referral diagnoses, sex, number of clinic visits and incidence of genetic testing in a population of individuals attending the CGC. Setting: Tertiary referral hospital (Royal Melbourne Hospital) providing cardiac genetics services to the state of Victoria. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The notion of multidisciplinary clinics was successfully implemented in other fields of medicine as well. Zentner et al have described their multidisciplinary cardiac genetics clinic over 6 years of follow-up (Zentner et al 2015). A total of 1170 patients were seen; genetic tests were obtained from 32.6% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of multidisciplinary clinics was successfully implemented in other fields of medicine as well. Zentner et al have described their multidisciplinary cardiac genetics clinic over 6 years of follow-up (Zentner et al 2015). A total of 1170 patients were seen; genetic tests were obtained from 32.6% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven percent of referrals had a confirmed genetic defect; however, the study did not include trisomies 13 and 18, which would have raised the number of positive cases. A similar study on adult cardiac patients showed a yield of 47.6% [ 14 ]. Since not all patients in the cardiology clinic are screened, the figure may be higher than described in the study.…”
Section: Discussionmentioning
confidence: 98%